Ugly Singaporeans - Chang, Vivienne Wei Ling (2014)
'Ugly Singaporeans' is a Singaporean sitcom featuring Singapore with a futuristic twist. It is the year 2023, Singapore is now divided into the East End, where foreigners and rich locals live, and the West End, home to the working-class Singaporeans. Follow the lives of two West-Enders, Ben and Aaron, as they navigate the waters of a divided Singapore. It is 25-minutes of satirising issues of xenophobia, censorship and other Singaporean complaints. The series is fronted by trademark Singaporean mannerisms that will prove to be anything but ugly.